Management of lymph nodes in medullary thyroid carcinoma: A review. (September 2022) - Shaghaghi, Ali; Salari, Abolfazl; Jalaeefar, Amirmohsen; Shirkhoda, Mohammad
Abstract: Introduction: Medullary Thyroid Carcinoma (MTC) as a neuroendocrine tumor that arises from the parafollicular C-cells and shows a potentially aggressive behavior with early lymph node metastasis. MTC cells do not absorb radioactive iodine and are not sensitive to Thyroid Stimulating Hormone (TSH) suppression, and therefore surgery is the most effective option for curative therapy. Results: Medical imaging and biomarkers (calcitonin & CEA) assessment are necessary to determine the appropriate approach to lymph nodes surgery in MTC. Prophylactic central, lateral or contralateral neck dissections are recommended based on calcitonin level and volume of tumor. In general, guidelines are in agreement with prophylactic central dissection in most cases. Central and lateral dissections are recommended in all guidelines and review articles if lymphadenopathy is confirmed in preoperative examinations. Because lymph node dissection in most cases of locally advanced or metastatic MTC has no prognostic effect, dissection is done with palliative goal with maximum attention to maintaining function in these cases. In patients with an incomplete lymph node dissection, decision for reoperation can be based on calcitonin levels and the number of metastatic lymph nodes removed in previous surgery. Symptoms as well as speed of disease progression are also important in adopting the type of surgery. Consensus is in favor of reoperation in patients with recurrent regional MTC without distant metastasis. Conclusion: Thyroidectomy is mandatory in patients with MTC but the type and extension of lymph node dissection are depending on the calcitonin level and tumor burden. Highlights: Surgery is the most effective treatment option for MTC. Prophylactic central, lateral or contralateral neck dissections are recommended based on calcitonin level. Therapeutic central and lateral dissection is recommended if lymphadenopathy is confirmed. In locally advanced or metastatic MTC dissection is done with maximum attention to maintaining function.